Sexual dysfunctions and associated factors in women of reproductive age - Bahrami, Nosrat; Alizadeh, Sima; Bahrami, Somayeh (Advances in Nursing & Midwifery, 2012)
Background and aim : Sexual function is associated with emotional-physiological, cultural and personal factors. World Health Organization recently defined sexual health as "the experience of the ongoing process of physical, psychological and sociocultural well-being related to sexuality. Sexual dysfunctions are particularly prevalent among women seeking routine gynecological care. Addressing sexual problems is an essential part of health care standards. The Aim of this study was to determine sexual satisfaction, sexual function disorders and associated factors in women of reproductive age who attended to Dezful health centers , Iran in 1387 .Data were analyzed by SPSS statistical software Material and Method: A descriptive- cross-sectional design was used. The sample of the study consisted of 250 women of reproductive age who attended to Health centers in Dezful ,Iran. Data were collected by a demographic questionnaire, and sexual function questionnaire . The validity of questionnaire was determined by content validity. Reliability was confirmed by test re-test. Findings: Mean score of total sexual function was 27/4 ± 7/3. The study findings showed that 64/6% of respondents had sexual dysfunction. There was also a significant correlation between sexual satisfaction and sexual function (p<0.001). The results of this study indicated that the majority of participations (78/6%) experienced good sexual satisfaction. Domain of sexual desire and sexual function indicated significant correlation with age, marriage age and educational level (p<0.05). Conclusion: The findings of this study indicated that inability at induce a health communication and pleasure with sexual wife is followed physical, psychological and social disorder for woman and her wife. Young couple education can caused correct recognition from sexual communication at pre marriage counsels. The findings of this study indicated that prevalence of sexual dysfunction are high, hence survey both men and women is essential and important. Keyword : Sexual function, Sexual dysfunction Female sexual disorders.